El año que soñamos peligrosamente - Žižek, Slavoj; Antón Fernández, Antonio J.; Žižek, Slavoj (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2013)
Call it the year of dreaming dangerously: 2011 caught the world off guard with a series of shattering events. While protesters in New York, Cairo, London, and Athens took to the streets in pursuit of emancipation, obscure destructive fantasies inspired the world's racist populists in places as far apart as Hungary and Arizona, achieving a horrific consummation in the actions of mass murderer Anders Breivik. The subterranean work of dissatisfaction continues. Rage is building, and a new wave of revolts and disturbances will follow. Why? Because the events of 2011 augur a new political reality. These are limited, distorted--sometimes even perverted--fragments of a utopian future lying dormant in the present.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed September 9, 2016)
Keywords: Social history -- 21st century; Social conflict -- History -- 21st century; Social change -- History -- 21st century; Political participation; Government, Resistance to -- History -- 21st century; Electronic books